Integrated single-cell multiomics reveals novel immune candidate markers for post-traumatic coagulopathy - Zheng, Ping; Zhang, Ning; Ren, Dabin; Yu, Cong; Zhao, Bin; Bai, Qingke; Zhang, Yisong; Sun, Wanju (Frontiers in Immunology, 2023)
Post-traumatic coagulopathy (PTC) is a critical pathology in traumatic brain injury (TBI), however, its potential mechanism is not clear. To explore this in peripheral samples, we integrated single cell RNA-sequencing and T cell repertoire (TCR)-sequencing across a cohort of patients with TBI. Clinical samples from patients with more brain severity demonstrated overexpression of T cell receptor–encoding genes and less TCR diversity. By mapping TCR clonality, we found patients with PTC have less TCR clones, and the TCR clones are mainly distributed in cytotoxic effector CD8+T cell. In addition, the counts of CD8+ T cell and natural killer (NK) cells are associated with the coagulation parameter by WGCNA, and the granzyme and lectin-like receptor profiles are also decreased in the peripheral blood from TBI patients, suggesting that reduced peripheral CD8+ clonality and cytotoxic profiles may be involved in PTC after TBI. Our work systematically revealed the critical immune status in PTC patients at the single-cell level.